Financial Behavioral Intentions: Hedonism Lifestyle and Emotional Intelligence Among Collectors of Art Toys - Inanda Shinta Anugrahani (DINASTI RESEARCH, 2026)
This study aims to determine the influence of a hedonistic lifestyle and emotional intelligence on financial behavioral intentions among art toy collectors in Indonesia. The research method used was quantitative, utilizing multiple regression analysis. A convenience sampling method was used to obtain 124 respondents. This study is interesting because it uses the Theory of Planned Behavior to determine whether surprises in the form of secret items in a blind box can damage an individual's behavioral control. The results showed that a hedonistic lifestyle has a negative effect on financial behavioral intentions. Emotional Intelligence has a positive effect on financial behavioral intentions.